Genetically engineering self-organization of human pluripotent stem cells into a liver bud-like tissue using Gata6 - Patrick Guye (Nature Portfolio, 2016)
There has been limited success in generating tissues from human induced pluripotent stem cells (hiPSCs). Here, the authors genetically engineer expression of the transcription factor Gata6 in a single isogenic hiPSC population resulting in complex tissue structures that exhibit liver bud-like properties.